Neonatal Intensive Care - Lyn Acres (AOSIS, 1981)
THE events of the third trimester of pregnancy labour, delivery and the newborn period undoubtedly influence the whole of one's life. Old age excluded, the highest mortality rate occurs in the perinatal period.